Taxonomy of Clathria (Thalysias) (Demospongiae: Poecilosclerida: Microcionidae) from the Colombian Caribbean, with description of three new species - Zea, Sven; Rodríguez, Angélica; Martínez, Ana María (Zootaxa, 2014)
Thinly encrusting sponges are diverse and ecologically important, but their taxonomy is challenging. In the Greater Caribbean, the recognition of species of Clathria (Thalysias), most of which are encrusting, is still problematic. Here we describe and clarify the taxonomy of eight species, three new to science, from material collected mostly in Colombia. These are C. (T.) virgultosa, C. (T.) curacaoensis, C. (T.) venosa, C. (T.) minuta, C. (T.) oxeota, C. (T.) sulfocleistochela n. sp., C. (T.) chelosigmoidea n. sp., and C. (T.) opalina n. sp. Underwater color photographs are provided, together with drawings of spicules and skeleton, and SEM images of spicules. Two other well-established Caribbean species of the subgenus, vis. C. (T.) isodictyoides and C. (T.) collosclera (both from Curaçao) were not found in the studied material. A key for their identification is provided. Three more records, C. (T.) fascicularis Topsent, 1889, C. (T.) procera (Ridley, 1884) and C. (T.) basiarenacea (Boury-Esnault, 1973) are outlined for further study.